The Application of Process-Oriented Guided-Inquiry Learning (POGIL) Techniques through Lesson Study Activities in Educational Management Courses at English Education to Increase Learning Activity - Veny Agustini Prianggita (Universitas Mathla'ul Anwar Banten, 2020)
Facing the industrial revolution 4.0, Indonesian citizens are challenged to be ready to feel some changes in many sectors including education sector. That is why Faculty of Teacher Training and Education of Mathla’ul Anwar University of Banten, a study programme which will prepare the graduates for industrial era 4.0 should start designing a learning process in order to create the graduates who are ready to face technology era that will be headed. This learning process innovation can be started by changing the learning paradigm from Teacher Centered Learning (TCL) to Student Centered Learning (SCL). One of technique that can be used is POGIL (Process-oriented guided-inquiry learning). It is a collaborative learning (cooperative, integrated inquiry, metacognitive). To make POGIL technique work optimally, it can be done by doing some learning activities of Lesson Study. Lesson study is an educator profession guiding model through learning assessment collaboratively and sustainably according to collegiality principals and mutual learning to improve the learning quality and learning community. Learning activities through the POGIL technique, are thought to be able to help improve the metacognition skills of English language education students, one of which is by seeing the results of the level of student activity while studying. This research is aimed to find out the student’s activity by using POGIL technique through learning activities of Lesson Study. The research question of this article is how to increase student learning activities with the POGIL technique through LSLC? This research is descriptive statistical analysis. The populations in this research are 25 university students who take English Education Course. The data collecting technique was done by using questionnaire. After data collecting, normality testing was done by using Shapiro-Wilk testing (because the population is less than 100) with signification degree α = 5%, followed by T one-sample test.According to data processing result done by using SPSS version 25, it is concluded that the average is 82,24 and deviation standard is 4,47. Then the normality test is applied and we get Sig. for 0,549, because the amount of Sig. is more than 0,05 so that data has normal distribution. Then T one-sample test is applied, and we get tcount=1,734 at the significant level 5%. The number of ttable got from t distribution table with dk=25 is 1,708. So, according to the result of data processing and t distribution table, it is known that the score of tcount=1,734 > ttable=1,708 at the significant degree 5%. It can be concluded that by POGIL technique application through Lesson Study activity, 80% students become more active in learning activity process at the class.